2022
DOI: 10.1126/sciadv.abm7891
|View full text |Cite
|
Sign up to set email alerts
|

Tree dynamic response and survival in a category-5 tropical cyclone: The case of super typhoon Trami

Abstract: In the future with climate change, we expect more forest and tree damage due to the increasing strength and changing trajectories of tropical cyclones (TCs). However, to date, we have limited information to estimate likely damage levels, and nobody has ever measured exactly how forest trees behave mechanically during a TC. In 2018, a category-5 TC destroyed trees in our ongoing research plots, in which we were measuring tree movement and wind speed in two different tree spacing plots. We found damaged trees in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The model showed that stand orientation and gaps in the forest were not particularly important but one of the most important factors controlling wind damage in forests subjected to tropical storms is support from neighboring trees. This insight is confirmed by a recent paper looking at damage to a thinned forest stand in Japan from a typhoon (Kamimura et al, 2022).…”
supporting
confidence: 57%
“…The model showed that stand orientation and gaps in the forest were not particularly important but one of the most important factors controlling wind damage in forests subjected to tropical storms is support from neighboring trees. This insight is confirmed by a recent paper looking at damage to a thinned forest stand in Japan from a typhoon (Kamimura et al, 2022).…”
supporting
confidence: 57%
“…We showed that other wind properties like duration of strong wind speeds, gust factor, wind direction and air density are influential, too. Duration of strong winds is important because trees do not fail instantly but fail with repeated swaying that fractures the root/soil system and this process can take many hours (Kamimura et al, 2022). Gust factor and air density are also known to be critical components in calculations of tree wind damage risk (see Equations 4.4, 4.12 and 4.15 in (Quine, Gardiner and Moore, 2021)).…”
Section: Predictor Selectionmentioning
confidence: 99%
“…The loading due to these turbulent structures with higher energy and momentum can be accounted for in a gust factor (Hale et al, 2015;Chen et al, 2018;Holland et al, 2006;Usbeck et al, 2010). Since trees react to gusts like damped harmonic oscillators (Mayer, 1987;Gardiner, 1992), there has been considerable debate about whether the arrival frequencies of these coherent eddies could lead to resonant failure (Gardiner, 1995;Peltola, 1996); however, this does not happen (Schindler and Mohr, 2019;Schindler and Kolbe, 2020;Kamimura et al, 2022), probably due to the efficient damping of trees (Spatz and Theckes, 2013). Besides the drag force of a plant (Rudnicki et al, 2004;Queck et al, 2012;Vollsinger et al, 2005), the level of damage depends also on the acclimation of plants to the wind (Telewski, 1995;Nicoll et al, 2019), which is a function of the maximum wind speed (Bonnesoeur et al, 2016;Dèfossez et al, 2022).…”
Section: The Physics Of Fine-scale Interactions Between Surfaces and ...mentioning
confidence: 99%
“…The characteristics of the tree (height, diameter, canopy size, wood properties) and the tree resistance to uprooting and breakage are all affected by the level of wind exposure (Gardiner et al, 2016). Recent experimental measurements of tree damage during a super typhoon (Kamimura et al, 2022) have also shown that collisions between the crowns of individual trees and the crowns of their neighbours are extremely important in reducing tree movement during strong winds and contributing to their overall stability. These adaptations of plants to living in a windy environment must be considered when modelling the risk of wind damage to tree stands.…”
Section: The Physics Of Fine-scale Interactions Between Surfaces and ...mentioning
confidence: 99%